Motor development interventions for preterm infants: a systematic review and meta-analysis - Hughes, Anita J.; Redsell, Sarah A.; Glazebrook, Cris (American Academy of Pediatrics, 2016)
CONTEXTS: Preterm infants are at an increased risk of neurodevelopmental delay. Some studies report positive intervention effects on motor outcomes, but it is currently unclear which motor activities are most effective in the short and longer term.